Direct measure of dome seeing with a localized optical turbulence sensor. Issue 4 (8th February 2019) - Lai, Olivier; Withington, J Kanoa; Laugier, Romain; Chun, Mark
ABSTRACT: Dome seeing is a known source of image quality degradation for any telescope, but despite tremendous progress in wavefront control through the development of adaptive optics and environmental control through implementation of dome venting, surprisingly little is known about it quantitatively. Circumstantial evidence of prevalent, non-Kolmogorov dome turbulence inferred from turbulence profiles and PSF morphology observed with the1 maka wide-field adaptive optics system has motivated the development of a new type of optical turbulence sensor called AIR FLOW: Airborne Interferometric Recombiner - Fluctuations of Light at Optical Wavelengths. It is based on a non-redundant mask imaging interferometer that samples the optical turbulence passing through a measurement cell. The instrument measures the local 2D optical Phase Structure Function which is a useful tool to characterize different types of turbulence (Kolmogorov, diffusive turbulence, etc.). By fitting different models, it is possible to determine parameters such asC_n^2, r 0, L 0, or deviation from fully developed turbulence. The instrument was tested in the Canada France Hawaii Telescope dome and the University of Hawaii 2.2-m telescope (UH88) tube. It is ruggedized and sensitive enough to detect changes in the turbulent conditions with different dome vent configurations, as well as slow but large amplitude variations of the index of refraction in the tube of the UH88-inch telescope tube. It can be used to seek out local sources of turbulence inside and around the dome and can be used routinely in an operational setting without affecting observations to quantitatively characterize the local optical turbulence responsible for dome seeing. We believe the instrument could be used in real-time observatory control systems to configure vents and air handlers in ways that more effectively reduce dome seeing. We also believe it could be a tool for site surveys to evaluate dome seeing and dome seeing mitigation strategies in situ .